Morphometric characterization of fruits and seeds and morphological aspects of mangaba (Hancornia speciosa Gomes) germination and seedlings native to the savanna in Amapá state (Research, Society and Development, 2021)
The aim of this study was to describe and characterize the morphometry of fruits and seeds and the morphological aspects of mangaba (Hancornia speciosa) germination and seedlings native to the savanna in Amapá, Brazil. A sampling of 119 fruits and 500 seeds was performed to determine the dimensions of the fruits and seeds, longitudinal length, width, equatorial diameter, mass of seeds per fruit and number of seeds per fruit. Next, 200 seeds were used to describe the post-seminal development stages, being arranged in eight plastic trays with sand substrate in a partially shaded place with daily irrigation in the morning and in the afternoon. The relationships between the variables were determined from the Spearman’s rank correlation coefficient (rS). The fruit is a berry and fleshy, with varied shape and a dark yellow color. The seeds are discoid, flat and light brown in color. The biometric characteristics of H. speciosa fruits and seeds showed great variation, especially in relation to weight and number of seeds per fruit. Germination occurs at a high rate and is cryptocotyledonary epigeal, having good viability and speed for germination. Seedlings have simple eophylls, opposite an acuminate apex and attenuated base.